Peningkatan kemampuan koneksi matematis siswa dalam pembelajaran daring menggunakan pendekatan metaphorical thinking - Rohmah, Nur Nabilah Syahrur; Cahyani, Intan Dwi; Fatimah, Oryza Lisativani; Faradiba, Surya Sari (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
This study aimed to explore the ability of mathematical connections in online learning through the metaphorical thinking approach. The metaphorical thinking approach is a student’s thinking process by using metaphors in understanding a concept. The use of metaphors in learning mathematics is a process to link mathematical concepts with concepts already known to student in everyday life. This research use a descriptive qualitative research method. The subjects of this study were students of class VII A of Mts Putra-Putri Lamongan in the even semester of the 2020/2021 academic year, totalling 23 students. The research data were collectedd through test and interviews. Then the data were analyzed descriptively and qualitatively. The result showed that the avarage mathematical connection ability in onlie learning through the Metaphorical Thinking approach was very high.